The way the question is written, you could have almost anything in your hand. All they have to do is add to - 12.
-14 and 2
- 11 and - 1
-12 and 0
- 82 and 70
Answer:
see explanation
Step-by-step explanation:
Assuming you are factoring the expression
Given
4y² + 26y + 30 ← factor out 2 from each term
= 2(2y² + 13y + 15) ← factor the quadratic
Consider the factors of the product of the coefficient of the y² term and the constant term which sum to give the coefficient of the y- term.
product = 2 × 15 = 30 and sum = 13
the factors are 10 and 3
Use these factors to split the y- term
2y² + 10y + 3y + 15 ( factor the first/second and third/fourth terms )
= 2y(y + 5) + 3(y + 5) ← factor out (y + 5) from each term
= (y + 5)(2y + 3)
Thus
4y² + 26y + 30
= 2(y + 5)(2y + 3)
Answer:
The answer is 2
Step-by-step explanation:
Answer:
3.026 $
Step-by-step explanation:
3.4 × 0.89 = 3.026 $
Answer:
100 / 112
Step-by-step explanation:
100 miniuts is a part of 112 adn is not a fraction and it does not say to siplify so you should be good.